A Review on Hepatoprotective Effect of Chrysin: Preclinical Implications and Molecular Cascades Came into Focus - Talebi, Marjan; Talebi, Mohsen; Farkhondeh, Tahereh; Simal-Gandara, Jesus; İlgün, Selen and Pourbagher-Shahri, Ali Mohammad and Samini, Mohamad and Samarghandian, Saeed (Current Diabetes Reviews, 2024)
Chrysin, a flavone nutraceutical, possesses several beneficial pharmacological properties, which has gained much emphasis in recent years. The biological effects of chrysin are exerted due to impeding or activating multifarious cellular and molecular pathways. Our findings indicated that chrysin inhibited tumor progression in various cancer cell lines by repressing the formation of a sphere and upregulated protein expression of Src homology region 2 domain-containing phosphatase-1 (SHP-1), alleviating phosphorylated-signal transducer and activator of transcription 3 (p-STAT3) and transaction workflow innovation standards team1 (Twist1), sustaining phosphorylation of extracellular signal-regulated kinase 1/2 (ERK1/2) and endorsing mitogen-activated protein kinase kinase1 (MEK1) overexpression, increasing the cytochrome c release, mitochondrial reactive oxygen species (ROS) formation, matrix metalloproteinases (MMP) collapse, and caspase-3 activity, modulating p53/ B-cell lymphoma-2 (Bcl-2)/caspase-9 cascade, cyclooxygenase-2 (COX-2), nuclear factor kappa B proposition 65 (NF-kB p65) expression and also decreasing the expression of nuclear factor erythroid 2-related factor 2 (Nrf2). Chrysin prevented cyclophosphamide, doxorubicin, cisplatin, methotrexate, paracetamol, alcohol, carbon tetrachloride, tert-butyl hydroperoxide (tBHP) and thioacetamide. Chrysin has protective properties against oxidative stress, inflammation, hepatotoxicity, liver fibrosis, steatosis, and hepatocellular carcinoma.Chrysin's most common hepatoprotective biochemical and molecular mechanisms involve the ability to control enzyme synthesis, scavenge free radicals, boost the antioxidant response, induce apoptosis, and modify the synthesis of proinflammatory and profibrotic cytokines.Chrysin is a valuable nutraceutical with broad therapeutic feasibility, but to confirm its representative hepatoprotective potential, clinical studies are advised. It would also be interesting to use cutting-edge drug delivery techniques or include bio-enhancers.
Keywords: hepatoprotective